Factors affecting the well-being of adolescents living with unemployed parents in times of economic recession: Findings from the portuguese HBSC study - Frasquilho, Diana (2017)
Objectives: Using a national representative sample of adolescents with unemployed parents, this study examined which factors (sociodemographic and of satisfaction with family life and peers) are related to the negative effect of parents' unemployment on emotional well-being. Study design: Cross-sectional survey study. Methods: Data on adolescents (14.1 ± 1.7 years old), with at least one parent unemployed (n ¼ 1311, 53.2% girls), was provided by the Portuguese Health Behaviour in School-aged Children study. Descriptive statistics and logistic regression analyses were performed. Results: A high proportion of adolescents reported being emotionally affected by father's unemployment but not by their mother's. Older boys and older girls were more likely to report that their same-gender parent's unemployment situation (sons-fathers and daughters-mothers) has had a negative effect on their well-being. Girls from low socioeconomic status and with poor family satisfaction were more likely to report negative emotional well-being related to parental unemployment. Conclusions: This study presents evidence on factors that can shape adolescents' emotional well-being related to parents' unemployment situation. Given the recessionary context and high unemployment rates, these insights are valuable to assist the design of an action to improve the levels of well-being of Portuguese adolescents from unemployed families.